Major blood vessels (Henry Stewart Talks, 2026)
Major blood vessels and circulatory network, Arteries vs veins, Systemic and pulmonary circulation, Major arteries and veins roles, Blood flow and pressure regulation, Blood vessels in organ function and disease, Vessel anatomy for diagnosis and treatment